2018
DOI: 10.1073/pnas.1806950115
|View full text |Cite
|
Sign up to set email alerts
|

Active sites for tandem reactions of CO 2 reduction and ethane dehydrogenation

Abstract: Ethylene (CH) is one of the most important raw materials for chemical industry. The tandem reactions of CO-assisted dehydrogenation of ethane (CH) to ethylene creates an opportunity to effectively use the underutilized ethane from shale gas while mitigating anthropogenic CO emissions. Here we identify the most likely active sites over CeO-supported NiFe catalysts by using combined in situ characterization with density-functional theory (DFT) calculations. The experimental and theoretical results reveal that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 31 publications
7
96
0
Order By: Relevance
“…However, on a surface that contained a greater amount of Ni than Fe, it was inferred that metallic Ni particles would be more pronounced. This could essentially dampen the catalytic effect observed with oxidized Fe, thereby changing the active site and promoting activity in favor of the dry reforming reaction, similar to those described previously for the reactions of CO 2 with ethane …”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…However, on a surface that contained a greater amount of Ni than Fe, it was inferred that metallic Ni particles would be more pronounced. This could essentially dampen the catalytic effect observed with oxidized Fe, thereby changing the active site and promoting activity in favor of the dry reforming reaction, similar to those described previously for the reactions of CO 2 with ethane …”
Section: Resultssupporting
confidence: 61%
“…From previous synchrotron X‐ray diffraction experiments we have confirmed that the CeO 2 support is crystalline and approximately 33 nm in size . In addition, under reaction conditions for the reduction of CO 2 with ethane the CeO 2 lattice has been shown to undergo abrupt expansions indicating an increase of the average CeO bond length due to the partial reduction of Ce 4+ to Ce 3+ . The BET surface area of the support has been reported by our group to be 49.1 m 2 g −1 while the Ni 3 Pt 1 /CeO 2 catalyst has a surface area of 44.5 m 2 g −1 …”
Section: Methodsmentioning
confidence: 52%
See 1 more Smart Citation
“…The implementation of CO 2 reduction always requires sufficient energy inputs and appropriate catalysts. Depending on the form of energy inputs (heat, electricity, radiation), CO 2 reduction is generally divided into thermo‐, electro‐, and photocatalytic reactions . The energy cost is relatively high and the product selectivity is uncontrollable in the thermocatalytic reduction of CO 2 , whereas the conversion is low in both electro‐ or photocatalytic CO 2 reduction .…”
Section: Introductionmentioning
confidence: 99%
“…Reaction 1), while pure dehydrogenation leads to H2 as a product (Reaction 3) 7,14,19,21,52 . However, the amount of hydrogen in the reactor effluent is also influenced by the extent of reverse water- In the case where direct dehydrogenation (Reaction 3) is the sole contributor to olefin formation, this ratio is expected to have a value equal to one.…”
Section: Effect Of Support and Active Sites On C2h6 Conversion Pathwaysmentioning
confidence: 99%